Políticas pública de educação ambiental: o caso do projeto Criança Ecológica na Floresta de Bebedouro. Bebedouro/SP - Fernandes, Alessandra Nicolau Pinheiro (2016)
Currently, public policy development adopted the idea of building a sustainable society. Thus, for the development of these policies, one can not disregard the relationship between man and nature that dictate what is possible in the face of what is desirable. In a sustainable society, progress must be seized by the quality of life and not for the pure material consumption. Being the focus of environmental concern of this new trend, environmental education is key to that sustainability is achieved. Public policies for environmental education should then guide for recognizing the fundamental ecological limitation of resources, without which no human activity can take place. Being eco-pedagogy a movement that aims to merge pedagogy and sustainability, which seeks to educate the sense and to the whole, then the environmental education projects adopted as public policy should be based on the concepts proposed by this aspect of EA focused on pedagogical practice that emphasizes learning with meaning, which arises from everyday situations and appreciates the sentiment, emotion and even spirituality in the educational process. It was in this perspective that the Strategic Project Ecological Child adopted by the State Government of São Paulo as public policy on environmental education and deployed in Forest Trough has been interpreted in this study. It was intended to examine the methodology and pedagogical Project from the target audiencechildren 8-10 years evaluating the use of ecopedagogy.